Multiferroicity in an organic charge-transfer salt that is suggestive of electric-dipole-driven magnetism - Lunkenheimer, Peter; Müller, Jens; Krohns, Stephan; Schrettle, Florian; Loidl, Alois; Hartmann, Benedikt; Rommel, Robert; De Souza, Mariano [UNESP]; Hotta, Chisa; Schlueter, John A.; Lang, Michael (Springer Nature, 2012)
Multiferroics, showing simultaneous ordering of electrical and magnetic degrees of freedom, are remarkable materials as seen from both the academic and technological points of view. A prominent mechanism of multiferroicity is the spin-driven ferroelectricity, often found in frustrated antiferromagnets with helical spin order. There, as for conventional ferroelectrics, the electrical dipoles arise from an off-centre displacement of ions. However, recently a different mechanism, namely purely electronic ferroelectricity, where charge order breaks inversion symmetry, has attracted considerable interest. Here we provide evidence for ferroelectricity, accompanied by antiferromagnetic spin order, in a two-dimensional organic charge-transfer salt, thus representing a new class of multiferroics. We propose a charge-order-driven mechanism leading to electronic ferroelectricity in this material. Quite unexpectedly for electronic ferroelectrics, dipolar and spin order arise nearly simultaneously. This can be ascribed to the loss of spin frustration induced by the ferroelectric ordering. Hence, here the spin order is driven by the ferroelectricity, in marked contrast to the spin-driven ferroelectricity in helical magnets. © 2012 Macmillan Publishers Limited. All rights reserved.
Keywords: Antiferromagnetic spins; Antiferromagnets; Charge orders; Charge-transfer salts; Different mechanisms; Electrical dipoles; Ferroelectric ordering; Helical magnets; Inversion symmetry; Multiferroics; Spin frustrations; Spin order; Antiferromagnetic materials; Charge transfer; Ferroelectric materials; Ferroelectricity